2021
DOI: 10.3389/fimmu.2021.653358
|View full text |Cite
|
Sign up to set email alerts
|

Roles of the Dynamic Tumor Immune Microenvironment in the Individualized Treatment of Advanced Clear Cell Renal Cell Carcinoma

Abstract: Immune checkpoint inhibitors (ICIs) are currently a first-line treatment option for clear cell renal cell carcinoma (ccRCC). However, recent clinical studies have shown that a large number of patients do not respond to ICIs. Moreover, only a few patients achieve a stable and durable response even with combination therapy based on ICIs. Available studies have concluded that the response to immunotherapy and targeted therapy in patients with ccRCC is affected by the tumor immune microenvironment (TIME), which ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 181 publications
(174 reference statements)
0
18
0
Order By: Relevance
“…The immune microenvironment of ccRCC has received considerable attention as increasing evidence suggested that it plays a crucial role in anti-cancer immunity ( 71 ). Previous studies have shown that ccRCC were inflammatory tumors accompanied by high infiltration of exhausted CD8 + TILs and immunosuppressive cells ( 72 ). We found high infiltration levels of CD8 + TILs and Tregs in early ccRCC, and increasing PDCD1 and LAG-3 levels with ccRCC progression in both cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…The immune microenvironment of ccRCC has received considerable attention as increasing evidence suggested that it plays a crucial role in anti-cancer immunity ( 71 ). Previous studies have shown that ccRCC were inflammatory tumors accompanied by high infiltration of exhausted CD8 + TILs and immunosuppressive cells ( 72 ). We found high infiltration levels of CD8 + TILs and Tregs in early ccRCC, and increasing PDCD1 and LAG-3 levels with ccRCC progression in both cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…As one of the most immunologically distinct tumor types, ccRCC exhibited the highest angiogenesis score and is frequently infiltrated with immune cells when compared with other epithelial cancer types ( 71 ). The extent of T-cell infiltration is remarkably high in ccRCC ( 72 ), which leads to marked inflammatory features. However, as the most abundant immune cells, CD8 + T cells display impaired anti-tumor effects, which indicates that the immune microenvironment for ccRCC is unique compared with other tumors ( 73 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that 25–30% of ccRCC patients already had distant metastases at the time of initial diagnosis [ 51 ]. So far, angiogenesis inhibition with tyrosine kinase inhibitors (TKIs) combined with the inhibition of immune checkpoint proteins such as PD-1/PDL-1 and CTLA-4 have revolutionized the treatment landscape of ccRCC patients with metastases [ 52 , 53 ]. However, the responses are limited to a subgroup of patients and only approximately 5 to 30% of patients will primarily progress [ 54 ].…”
Section: Discussionmentioning
confidence: 99%